Tailored Nanoscale Plasmon-Enhanced Vibrational Electron Spectroscopy - Tizei, Luiz H. G. (Nano Lett, 2020)
[Image: see text] Atomic vibrations and phonons are an excellent source of information on nanomaterials that we can access through a variety of methods including Raman scattering, infrared spectroscopy, and electron energy-loss spectroscopy (EELS). In the presence of a plasmon local field, vibrations are strongly modified and, in particular, their dipolar strengths are highly enhanced, thus rendering Raman scattering and infrared spectroscopy extremely sensitive techniques. Here, we experimentally demonstrate that the interaction between a relativistic electron and vibrational modes in nanostructures is fundamentally modified in the presence of plasmons. We finely tune the energy of surface plasmons in metallic nanowires in the vicinity of hexagonal boron nitride, making it possible to monitor and disentangle both strong phonon–plasmon coupling and plasmon-driven phonon enhancement at the nanometer scale. Because of the near-field character of the electron beam–phonon interaction, optically inactive phonon modes are also observed. Besides increasing our understanding of phonon physics, our results hold great potential for investigating sensing mechanisms and chemistry in complex nanomaterials down to the molecular level.